Pengaruh Kesadaran, Tingkat Pengetahuan, Sanksi Perpajakan, dan Lingkungan Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi: (Studi Kasus di Kantor Pelayanan Pajak Pratama Kudus Tahun 2018) - Purwati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
Abstract Tax is one of the state revenues that is used to continue to carry out national development in order to realize the welfare of all Indonesian people. This study aims to analyze how the influence of awareness, level of knowledge, tax sanctions, and the environment of taxpayers on individual taxpayer compliance with case studies at the Holy Pratama Tax Service Office in 2018. This type of research is case study and field research (Case Study and Field Research The approach used in this study is a quantitative approach.Taking of samples in this study using Simple Random Sampling techniques.The samples to be taken in this study were 100 respondents.The data analysis method used was multiple linear regression with the help of SPSS version 23.00 The results showed that the variable of consciousness affected the taxpayer compliance based on the calculation, it was obtained tcount> ttable, that is 3.048> 1.66105 with a significance level of 0.003. bro, obtained t count> t table is 2.057> 1.66105 with a significance level of 0.042. Variable tax sanctions affect the taxpayer compliance based on calculations obtained t count> t table that is 1.711> 1.66105 with a significance level of 0.090. Environmental variable taxpayers affect the taxpayer compliance based on the calculation obtained t count> t table that is 3.831> 1.66105 with a significance level of 0,000. Variable awareness (X1), level of knowledge (X2), taxation sanction (X3), and taxpayer environment (X4) based on the calculation, fcount> ftabel is 17,182> 2.00 with a significance level of 0,000. Then simultaneously the variables of awareness, level of knowledge, taxation sanctions, and the environment of taxpayers together affect the compliance of individual taxpayers in Kudus Primary Tax Office in 2018.